One piece. East Blue. Baroque Works. Vol. 12, The legend begins - Oda, Eiichiro, 1975-; Caselman, Lance; JN Productions (San Francisco, CA : VIZ Media, LLC, 2006)
After narrowly escaping execution at the hands of Lady Alvida and Buggy the Clown, Luffy now has the Navy on his trail, led by Captain Smoker, who has never let a pirate escape his jurisdiction.
"East Blue" refers to the story arc covered in v. 1 through 12 of the One Piece series.
"First published in Japan in 1997 by Shueisha Inc, Tokyo"--Page facing t.p.
"Parental advisory. One Piece is rated T for teen and is recommended for ages 13 and up. This v. contains fantasy violence and tobacco usage"--Page facing t.p.
"This book reads from right to left"--Back cover.
"This v. contains material that was originally published in English in Shonen Jump #42-44"--Page facing t.p.
Translated from the Japanese.
Keywords: Pirates -- Comic books, strips, etc. -- Fiction; Treasure troves -- Comic books, strips, etc. -- Fiction; Buried treasure -- Comic books, strips, etc. -- Fiction; Manga; Pirates -- Comic books, strips, etc. -- Fiction; Action and adventure comics; Graphic novels